2008
DOI: 10.1152/ajpheart.01103.2007
|View full text |Cite
|
Sign up to set email alerts
|

Role of asymmetric dimethylarginine for angiotensin II-induced target organ damage in mice

Abstract: RH, Hilgers KF. Role of asymmetric dimethylarginine for angiotensin II-induced target organ damage in mice. Am J Physiol Heart Circ Physiol 294: H1058-H1066, 2008. First published December 21, 2007 doi:10.1152/ajpheart.01103.2007.-The aim of the present study was to investigate the role of the endogenous nitric oxide synthase inhibitor asymmetric dimethylarginine (ADMA) and its degrading enzyme dimethylarginine dimethylaminohydrolase (DDAH) in angiotensin II (ANG II)-induced hypertension and target organ dama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
34
1
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 42 publications
6
34
1
3
Order By: Relevance
“…ADMA can be metabolized by DDAH‐1 and DDAH‐2, thereby increasing eNOS‐derived NO bioavailability 19, 20. Thus, DDAH deregulation, which causes ADMA accumulation, is also a risk factor for cardiovascular diseases 19, 20.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ADMA can be metabolized by DDAH‐1 and DDAH‐2, thereby increasing eNOS‐derived NO bioavailability 19, 20. Thus, DDAH deregulation, which causes ADMA accumulation, is also a risk factor for cardiovascular diseases 19, 20.…”
Section: Discussionmentioning
confidence: 99%
“…DDAH‐1 is predominately expressed in proximal tube kidney and in the liver, whereas DDAH‐2 is the predominant isoform in vascular cells 18, 19. Recent research found that overexpression of DDAH‐1 reduced ADMA levels and angiotensin II–induced hypertension in mice 20. Additionally, overexpression of DDAH‐1 ameliorated atherosclerosis by lowering ADMA level in apolipoprotein E–deficient (apoE −/− ) mice 21.…”
Section: Introductionmentioning
confidence: 99%
“…ADMA or L-NAME infusion into mice exacerbated renal fibrosis, but both raised SBP by approximately 60 mmHg, suggesting hypertensive injury 28 ; global DDAH1 overexpression, however, protected against fibrosis in angiotensin and surgical nephron-reduction models of CKD. 29,30 Genetic DDAH1 overexpression decreases circulating ADMA and introduces unmeasured effects upon normal regulatory mechanisms. Furthermore, DDAH1 overexpression occurs indiscriminately in cell types that do not normally express DDAH1, but play significant roles in inflammation and fibrosis (e.g., macrophages).…”
Section: Discussionmentioning
confidence: 99%
“…There are also conflicting reports on the effects of administration of exogenous ANG II on ADMA in vivo. Whereas Hasegawa and colleagues (14) showed that 2 wk of ANG II infusion in mice resulted in a 100% increase in plasma ADMA, Jacobi et al (19) found no effect of 4 wk of ANG II infusion on plasma ADMA levels. These studies did not examine the effects of ANG II infusion on tissue levels of ADMA.…”
mentioning
confidence: 97%